2021
DOI: 10.1186/s12913-021-06405-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of services provided by health centers in Mashhad, Iran: SERVQUAL versus HEALTHQUAL scales

Abstract: Background Primary health care is the entry point to the health-care system and regarded as an essential step to achieving universal health coverage. The present study aimed at evaluating the quality of health-care services provided in health centers in Mashhad, Iran. Methods This was a cross-sectional study implemented among 200 health service users who were referring to four health centers in Mashhad during January to June 2019. The quality of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
5
21
0
Order By: Relevance
“…As for the tangibility dimension, based on the statistical analysis, users' expectations are found to exceed their perception, as evidenced by the users' perception of low service quality in the tangibility dimension. This result supports the view that SERVQUAL as a tool can attract the attention of service providers [12] due to its ability to identify gaps in service quality. Compared to other studies, clients' expectations in this study for the dimension of tangibility appear to be rather high, but the actual gaps are smaller compared to other studies [13][14][15][16].…”
Section: Discussionsupporting
confidence: 84%
“…As for the tangibility dimension, based on the statistical analysis, users' expectations are found to exceed their perception, as evidenced by the users' perception of low service quality in the tangibility dimension. This result supports the view that SERVQUAL as a tool can attract the attention of service providers [12] due to its ability to identify gaps in service quality. Compared to other studies, clients' expectations in this study for the dimension of tangibility appear to be rather high, but the actual gaps are smaller compared to other studies [13][14][15][16].…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the result of P-E gap measurement showed a negative value, indicating that the patient's expectations for services had not been met fully. Similar studies in hospitals in Riyadh and Pakistan reported the same results, where all aspects still had a negative P-E gap (Aghamolaei et al 2014, Al-Momani 2016, Fatima et al 2018, Sharifi et al 2021. Patient satisfaction is influenced by expectations, and patient perceptions that have not been fully explained because the marketing-oriented conceptual model is not always appropriate for various health care conditions.…”
Section: Resultsmentioning
confidence: 72%
“…The main purpose of improvement dimension is to measure whether the medical services meet the needs of patients and whether the patient feels satisfied during and after providing the services. Sharifi ( 54 ) called this dimension “effectiveness” which is related to patient's goals in receiving the appropriate and complete treatment from the hospital. The results in Table 4 above show the dissatisfaction of respondents from this dimension from both hospitals with a mean of (1.81 ± 0.65) for the private hospitals in comparison to (1.37 ± 0.63) for the public hospitals.…”
Section: Resultsmentioning
confidence: 99%